O dano existencial decorrente da prática de alienação parental: um diálogo entre a responsabilidade civil e o direito de família - OLIVEIRA, Grace Baêta de (Universidade Federal do Pará, 2023)
The evolution of Civil Liability in contemporary society also reaches the Family Law, by prioritizing the dignity of the human person, and therefore, the existential interests of the child and adolescent, central figures in the practice of parental alienation in cases of litigious divorces, which they become victims of resentful parents, who abuse parental power, violating constitutional rights, such as the right to live together. Based on this new perspective, the Civil Liability Institute faces the challenge of contributing to the necessary recognition of new types of damages, covered by the generic name of moral damage, because in addition to the strictly moral perspective, other interests make up the sphere of an individual, in training, which needs differentiated tutelage and that meets the principle of the best interest of children and adolescents. The present research, therefore, presents the importance of recognizing existential damage, as an autonomous category of damage, in family relationships, based on the cases in which the violation of the right to coexistence is identified, aggravated by the action of time, which possibly it may damage life relationships, the parenting project and the right to children's identity. Thus, from the dialogue between Family Law and Civil Liability, through the study of existential damage, the primary objective is to demonstrate its occurrence in cases where the alienating phenomenon is configured, and at the same time, ascertain whether Liability presents itself as an effective institute to curb abusive parenting practices or at least contribute to its reduction. The methodology used is bibliographic and documentary, using the analysis of decisions, of qualitatively selected cases, and the understanding contained in judgments about off-balance sheet damage, in the face of the violation of the duty of care. It was observed that the extension of moral damage does not reach all the off-balance sheet interests of the human person. The generic character coupled with the lack of reasoning may not justly protect the damage experienced.